Prospective Evaluation of the Patient Acceptable Symptom State to Identify Clinically Successful Anterior Cruciate Ligament Reconstruction. Issue 5 (April 2019) - Vega, José F.; Jacobs, Cale A.; Strnad, Gregory J.; Farrow, Lutul; Jones, Morgan H.; Miniaci, Anthony; Parker, Richard D.; Rosneck, James; Saluan, Paul; Williams, James S.; Spindler, Kurt P.
Background: The length of most patient-reported outcome measures creates significant response burden, which hampers follow-up rates. The Patient Acceptable Symptom State (PASS) is a single-item, patient-reported outcome measure that asks patients to consider all aspects of life to determine whether the state of their joint is satisfactory; this measure may be viable for tracking outcomes on a large scale. Hypothesis: The PASS question would identify clinically successful anterior cruciate ligament reconstruction (ACLR) at 1-year follow-up with high sensitivity and moderate specificity. We defined "clinically successful" ACLR as changes in preoperative to postoperative scores on the Knee injury and Osteoarthritis Outcome Score (KOOS) pain subscale and the KOOS knee-related quality of life subscale in excess of minimal clinically important difference or final KOOS pain or knee-related quality of life subscale scores in excess of previously defined PASS thresholds. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Patients enrolled in a prospective longitudinal cohort completed patient-reported outcome measures immediately before primary ACLR. At 1-year follow-up, patients completed the same patient-reported outcome measures and answered the PASS question: "Taking into account all the activity you have during your daily life, your level of pain, and also your activity limitations and participation restrictions, do you consider the current state of your knee satisfactory?" Results: A total of 555 patients enrolled in our cohort; 464 were eligible for this study. Of these, 300 patients (64.7%) completed 1-year follow-up, of whom 83.3% reported satisfaction with their knee after surgery. The PASS question demonstrated high sensitivity to identify clinically successful ACLR (92.6%; 95% CI, 88.4%-95.6%). The specificity of the question was 47.1% (95% CI, 35.1%-59.5%). The overall agreement between the PASS and our KOOS-based criteria for clinically successful intervention was 81.9%, and the kappa value indicated moderate agreement between the two methods (κ = 0.44). Conclusion: The PASS question identifies individuals who have experienced clinically successful ACLR with high sensitivity. The limitation of the PASS is its low specificity, which we calculated to be 47.1%. Answering "no" to the PASS question meant that a patient neither improved after surgery nor achieved an acceptable final state of knee health. The brevity, interpretability, and correlation of the PASS question with significant improvements on various KOOS subscales make it a viable option in tracking ACLR outcomes on a national or global scale.